German Heart Surgery Report 2017: The Annual Updated Registry of the German Society for Thoracic and Cardiovascular Surgery - Beckmann, Andreas; Meyer, Renate; Lewandowski, Jana; Frie, Michael; Markewitz, Andreas; Harringer, Wolfgang (The Thoracic and Cardiovascular Surgeon, 2018)
Based on a longtime voluntary registry, founded by the German Society for Thoracic and Cardiovascular Surgery (GSTCVS), well-defined data of all cardiac, thoracic, and vascular surgery procedures performed in 78 German heart surgery departments during the year 2017 are analyzed. In 2017, a total of 179,337 procedures were submitted to the registry, and 101,728 were summarized as heart surgery procedures in the narrower sense. About 16.8% of these patients were at least 80 years old, resulting in an increase of 1.1% compared with the data of 2016. The 36,273 isolated coronary artery bypass grafting procedures (relationship on-/off-pump 4.2:1) were associated with an unadjusted in-hospital survival rate of 97.3%. Concerning the 34,394 isolated heart valve procedures (including 12,965 transcatheter interventions), the unadjusted in-hospital survival rate was 96.0%.This annual updated registry of the GSTCVS represents voluntary public reporting by accumulating actual information for nearly all heart surgical procedures in Germany, describes advancements in heart medicine, and is a basis for in- and external quality assurance for all participating institutions. In addition, the registry demonstrates that the provision of cardiac surgery in Germany is appropriate, and nationwide patient treatment is guaranteed at any time.
Keywords: heart valve surgery; outcomes; congenital heart disease; CHD; aorta; coronary artery bypass grafting; CABG; arrhythmia therapy